Entrepreneurship education on entrepreneurial intention: The moderating role of the personality and family economic status - Liu, Yiran; Li, Min; Li, Xin; Zeng, Jingyi (Frontiers in Psychology, 2022)
This study investigates the impact of entrepreneurship education on college students’ entrepreneurial intentions, as well as the moderating effects of personality and family economic status on the relationship between entrepreneurship education and entrepreneurial intention, respectively. We tested our hypotheses using a sample of college students in Tianjin, China, and analyzed the data of 326 questionnaires containing validated measures. The results show that entrepreneurship education has a positive impact on college students’ entrepreneurial intentions; proactive personality negatively moderates this relationship; and family economic status positively moderates it. However, the moderating effect of narcissistic personality has not been verified. This study is unique and innovative as it brings new insights to this stream of literature by introducing the roles of the personality and family economic status in the relationship between entrepreneurship education and entrepreneurial intention. Our analysis provides important empirical evidence about the negative moderating effect of proactive personality and the positive moderating effect of family economic status on the relationship between entrepreneurship education and entrepreneurial intention, introducing insights into the heterogeneity of the effect of entrepreneurship education.